Ferroelectric Transformer (Global Journal of Science Frontier Research, 2018)
In the article is described the ferroelectric transformer, which in contrast to the transformer with the ferromagnetic of cores can work at the high frequencies. Such previously transformers were not known. This opens prospects the creation of wide-band ferroelectric amplifiers.
Keywords: transformer; ferroelectric; ferroelectric transformer; amplifier